The effect of host genetics on the gut microbiome - Bonder, Marc Jan; Kurilshikov, Alexander; Tigchelaar, Ettje F; Mujagic, Zlatan; Imhann, Floris; Vila, Arnau Vich; Deelen, Patrick; Vatanen, Tommi; Schirmer, Melanie; Smeekens, Sanne P; Zhernakova, Daria V; Jankipersadsing, Soesma A; et al. (Nature genetics, 2016)
Alexandra Zhernakova, Jingyuan Fu, Cisca Wijmenga and colleagues perform genome-wide association analysis for microbiome characteristics in a cohort with fully sequenced metagenomes and detailed diet and lifestyle data. They find loci significantly associated with different microbial species, pathways and genes and examine specific gene–diet interactions. The gut microbiome is affected by multiple factors, including genetics. In this study, we assessed the influence of host genetics on microbial species, pathways and gene ontology categories, on the basis of metagenomic sequencing in 1,514 subjects. In a genome-wide analysis, we identified associations of 9 loci with microbial taxonomies and 33 loci with microbial pathways and gene ontology terms at P < 5 × 10 −8 . Additionally, in a targeted analysis of regions involved in complex diseases, innate and adaptive immunity, or food preferences, 32 loci were identified at the suggestive level of P < 5 × 10 −6 . Most of our reported associations are new, including genome-wide significance for the C-type lectin molecules CLEC4F – CD207 at 2p13.3 and CLEC4A – FAM90A1 at 12p13. We also identified association of a functional LCT SNP with the Bifidobacterium genus ( P = 3.45 × 10 −8 ) and provide evidence of a gene–diet interaction in the regulation of Bifidobacterium abundance. Our results demonstrate the importance of understanding host–microbe interactions to gain better insight into human health.